BERBAGI PENGALAMAN MENGAJAR SAAT PANDEMI COVID-19 DENGAN PARA GURU SEKOLAH DASAR DI DESA SINGAPADU KALER SUKAWATI GIANYAR - Anak Agung Gede Duwira Hadi Santosa; Made Suksma Prijandhini Devi Salain; Anak Agung Sri Utari; I Gde Putra Ariana; Made Maharta Yasa (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The purpose of this service is to share experiences regarding online learning strategies to increase motivation and activeness of elementary school students, and to share experiences about online learning media and how to use them in supporting teaching and learning activities for elementary school students. The online learning system tend to reduce the motivation and activity of elementary school students, and make students become lazy to study. To overcome this situation, it is necessary to modify the learning strategies by teachers. Online learning carried out by several elementary schools in Singapadu Kaler village encountered several technical and non-technical obstacles, namely facility resources which is learning media that were too complicated, making it difficult for teachers and parents of students, as well as human resources obstacle, namely teachers who were less proficient in the use of online learning media and busy parents which resulting in limited devices that can be used by their children. This service uses the methods such as delivering online teaching experiences by members of the International Law Department, Faculty of Law, Udayana University, as well as questions and answers to obtain results and solutions as a form of solving problems and obstacles faced by teachers in conducting online learning during the Covid-19 pandemic.